TINJAUAN TERHADAP BARANG BAWAAN TAMU PADA ACARA BARALEK DI KENAGARIAN VII KOTO TALAGO KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Supriani, Nike; Baidar, Baidar; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2016)
Study this is aimed to identify the contents, the equipment used, determine the function and meaning luggage of guest at the wedding party. This study was descriptive qualitative research with the object luggage of guest. Data collected by using Snowball Sampling, included observation, interviews, and documentation. Data analysis include reduction data, presentation of data, and verification conclusion. Showed the result the difference between the luggage of invited guest and guest were called. Invited guest brought 3 tray of food and 1 basket of rice contain rice and gifts. Luggage of guest filled by the host with food. Guest were called bring rice and glutinous rice, then luggage of guest filled by the host with bananas, pinyaram, fish cake, sugar, and instant noodles. Luggage of guest functioning to eased the burden of the host and strengthen family relationships between many people. Its meaning as keeping feelings, generous, and know the customs is characteristic of the minang people.Keyword: Luggage, Wedding Party, Kenagarian VII Koto Talago